Inputs and sources of Pb and other metals in urban area in the post leaded gasoline era. (1st August 2022) - Ye, Jiaxin; Li, Junjie; Wang, Pengcong; Ning, Yongqiang; Liu, Jinling; Yu, Qianqian; Bi, Xiangyang
Abstract: The contamination status of heavy metals in urban environment changes frequently with the industrial structure adjustment, energy conservation and emission reduction and thus requires timely investigation. Based on enrichment factor, multivariate statistical analysis and isotope fingerprinting, we assessed comprehensively the inputs and sources of heavy metals in different samples from an urban area that was less impacted by leaded gasoline exhaust. The road dust contained relatively high levels of Cr, Pb and Zn (with enrichment factor >2) that originated from both exhaust and non-exhaust traffic emissions, while the moss plants could accumulate high levels of Pb and Zn from the deposition of traffic exhaust emission. This suggest that the traffic emission is still an important source of metals in the urban area although gasoline is currently lead free. On the contrary, the occurrences of metals in the urban soils were controlled by natural sources and non-traffic anthropogenic emission. These findings revealed that different samples would receive different inputs of metals from different sources in the urban area, and the responsiveness and sensitiveness of these urban samples to metal inputs can be ranked as moss ≥ dust > soil. Taken together, our results suggested that in order to avoid generalizing and get detail source information, multi-samples and multi-measures must be adopted in the assessment of integrated urban environmental quality. Graphical abstract: Image 1 Highlights: Multivariate statistics analysis, GIS and Pb isotope were used to trace metal sources. Traffic exhaust is still an important source of heavy metals in urban environment. Different samples showed different sensitivities to different metal inputs. Multi samples and measures are needed in integrated urban environmental assessment.